Conditional mutants of the yeast mRNA capping enzyme show that the cap enhances, but is not required for, mRNA splicing. - Fresco, L D (1996)
The 5' end of eukaryotic mRNAs are modified by the addition of a 7-methyl guanosine (m7G) cap. The role of the cap in translation has been well established. Additionally, studies conducted in vitro or in microinjected Xenopus oocytes have implicated the cap in RNA processing and transport. To determine the fate of uncapped mRNA in intact yeast cells, conditional alleles of the gene encoding the capping enzyme guanylyltransferase subunit (CEG1) were generated. RNA analysis of temperature-sensitive ceg1 strains revealed an accumulation of unspliced pre-mRNAs and a corresponding decrease in spliced mRNAs at the restrictive temperature. A substantial proportion of spliced mRNA was also uncapped. Therefore, the cap appears to stimulate, but is not absolutely required for, splicing in vivo. In addition, steady-state levels of several mRNAs were decreased, perhaps due to increased degradation of uncapped mRNAs. In contrast to splicing, mRNA polyadenylation and transport to the cytoplasm were unaffected.